A Morphological Study of the Meniscus, Cartilage and Subchondral Bone Following Closed-Joint Traumatic Impact to the Knee - Haut Donahue, T. L.; Narez, G. E.; Powers, M.; Dejardin, L. M.; Wei, F.; Haut, R. C. (Frontiers in Bioengineering and Biotechnology, 2022)
Post-traumatic osteoarthritis (PTOA) is a debilitating disease that is a result of a breakdown of knee joint tissues following traumatic impact. The interplay of how these tissues influence each other has received little attention because of complex interactions. This study was designed to correlate the degeneration of the menisci, cartilage and subchondral bone following an acute traumatic event that resulted in anterior cruciate ligament (ACL) and medial meniscus tears. We used a well-defined impact injury animal model that ruptures the ACL and tears the menisci. Subsequently, the knee joints underwent ACL reconstruction and morphological analyses were performed on the menisci, cartilage and subchondral bone at 1-, 3- and 6-month following injury. The results showed that the morphological scores of the medial and lateral menisci worsened with time, as did the tibial plateau and femoral condyle articular cartilage scores. The medial meniscus was significantly correlated to the medial tibial subchondral bone at 1 month (p=0.01), and to the medial tibial cartilage at 3 months (p=0.04). There was only one significant correlation in the lateral hemijoint, i.e. the lateral tibial cartilage to the lateral tibial subchondral bone at 6 months (p=0.05). These data may suggest that, following trauma, the observed medial meniscal damage should be treated acutely by means other than a full or partial meniscectomy, since that procedure may have been the primary cause of degenerative changes in the underlying cartilage and subchondral bone. In addition to potentially treating meniscal damage differently, improvements could be made in optimizing treatment of acute knee trauma.